2020
DOI: 10.3390/molecules25204615
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Enhancement of Farmed Salmon Meat via Non-GMO Nannochloropsis Gaditana: Eicosapentaenoic Acid (EPA, 20:5 n-3), Docosapentaenoic Acid (DPA, 22:5 n-3) and Vitamin D3 for Human Health

Abstract: Omega-3 long-chain polyunsaturated fatty acids (n-3 LC PUFAs) and vitamin D3 are essential components of human nutrition. A regular human diet is highly deficient in n-3 LC PUFAs. Fish like salmon are highly recommended in the human diet as they are a major source of high-value n-3 LC PUFAs and vitamin D3. The levels of these nutrients have been decreasing over the last few years in farmed salmon, whose production urgently needs sustainable sources of these nutrients. The microalga Nannochloropsis gaditana (NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Nannochloropsis sp. is a unicellular microalga with a polysaccharide cell wall (Hibberd 1981) and a promising ingredient in aquafeeds both as a successful fish oil substitute (Eryalçın and Yıldız 2015;Gbadamosi and Lupatsch 2018;Lozano-Muñoz et al 2020) and the form of the defatted meal as an alternative to fish meal (Sørensen et al 2017). Moreover, N. oceanica became better digested by European sea bass than other microalgae marine species (Batista et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Nannochloropsis sp. is a unicellular microalga with a polysaccharide cell wall (Hibberd 1981) and a promising ingredient in aquafeeds both as a successful fish oil substitute (Eryalçın and Yıldız 2015;Gbadamosi and Lupatsch 2018;Lozano-Muñoz et al 2020) and the form of the defatted meal as an alternative to fish meal (Sørensen et al 2017). Moreover, N. oceanica became better digested by European sea bass than other microalgae marine species (Batista et al 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, fish liver, fish liver oil, oily fish and seagull eggs have been major sources of vitamin D for the coastal population of Norway [ 147 ], with salmon being widely proposed as a good example of a fish source rich in both n-3 PUFA and vitamin D [ 148 , 149 ], while variations in vitamin D content and differences between wild and farmed salmon [ 149 ] also suggest further research to ensure a sustainable production of salmon with adequate vitamin D. Analysis of vitamin D content in various fish species indicated that the disproportion between requirement and supply seems too vast to enable eradication of vitamin D deficiency by fish food-based solutions. Still, increasing fish consumption or changing consumption patterns could be beneficial and result in noticeable improvements in vitamin D status [ 126 ].…”
Section: Fish Lipid Bioactives and Health Benefitsmentioning
confidence: 99%
“…DPA is an indispensable n-3 LC-PUFA found in large amounts in FO, and even larger amounts in salmon filets (0.4 g 100 g −1 filet) (Calder, 2018;Lozano-Muñoz et al, 2020). DPA has attracted recent attention due to its importance in human health.…”
Section: Introductionmentioning
confidence: 99%